Pengaruh Gaya Hidup dan Literasi Ekonomi terhadap Perilaku Konsumtif untuk Produk Fashion Mahasiswa Pendidikan Ekonomi FKIP UNS Angkatan 2021-2023 - Mardani, Adha Ratia; Harini, Harini; Nugroho, Jonet Ariyanto (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research aims to determine (1) Testing the influence of lifestyle on consumptive behavior for fashion products for FKIP UNS Economic Education students class 2021-2023 (2) Testing the influence of economic literacy on consumptive behavior for fashion products for FKIP UNS Economic Education students class 2021-2023 (3) Testing the influence of lifestyle and economic literacy simultaneously on consumer behavior for fashion products of FKIP UNS Economic Education students class 2021-2023. This research is quantitative research with a survey method. The population used in the research were FKIP Economics Education students class 2021, 2022 and 2023. The data collection method used was using a questionnaire distributed via Google Form with a population of 380 students and a sample of 195 students. The sampling technique uses purposive sampling. The analysis in this research uses multiple linear regression. The results of this study prove that (1) lifestyle has a positive and significant effect on consumptive behavior for fashion products (2) economic literacy has a negative and significant effect on consumptive behavior for fashion products (3) lifestyle and economic literacy has a positive and significant effect on consumptive behavior for fashion products.